Diagnostic and treatment errors in management of the bone metastases - Rolski, Janusz; Pawlicki, Marek (Contemporary Oncology/Współczesna Onkologia, 2004)
The increasing incidence of neoplastic diseases is correlated with the increase of population median age. The most frequent metastatic sites are lungs, liver and bones. The standard therapeutic approach to bone metastases involves the systemic treatment (chemotherapy, hormonotherapy, immunotherapy and supportive drugs such as biphosphonates), irradiation and surgery. In order to apply such a complex treatment several medical specialists must work closely together. The main goal of the palliative treatment is the improvement of the comfort of patient’s life, however, in some patients it may also extend their survival. There are several criteria that must be fulfilled before patients can be subjected to an aggressive treatment. These are: expected survival of >3 months, primary lesion cured or controlled, good performance status, approval of treatment by the patient who is aware of its duration, intensity and potential side effects. Moreover, due to a high progression risk the patient must be well informed. In the case of bone disruption or spine compression a surgical treatment should also be performed despite poor prognosis.